Quantitative Analysis of Morphometric Data of Pre-modern Birds: Phylogenetic Versus Ecological Signal - Bell, Alyssa; Marugán-Lobón, Jesús; Navalón, Guillermo; Nebreda, Sergio M.; DiGuildo, John; Chiappe, Luis M. (Frontiers in Earth Science, 2021)
Birds are one of the most diverse clades of extant terrestrial vertebrates, a diversity that first arose during the Mesozoic as a multitude of lineages of pre-neornithine (stem) birds appeared but did not survive into the Cenozoic Era. Modern birds (Neornithes) inhabit an extensive array of ecologically distinct habitats and have specific and varied foraging strategies. Likewise, the morphological disparity among Mesozoic lineages appears to underscore a significant degree of ecological diversity, yet attempts to determine lineage-specific ecologies have mainly been limited to superficial narratives. In recent years, numerous studies have used various morphometric proxies to interpret the paleoecology of Mesozoic bird lineages, but largely without evaluating the interplay between ecological and phylogenetic signals. Moreover, most studies of this sort transform the original data into logarithms to control dimensionality, underestimating the biases induced upon such transformations. The goal of this study is to quantitatively address the ecomorphology of crown-group Neornithes using a dense sample of raw forelimb and hindlimb measurements, and to examine if such results can be used to infer the ecologies of Mesozoic bird lineages. To that end, scaling of limb measurements and ecological data from modern birds was assessed statistically using phylogenetic comparative methods, followed by the inclusion of fossil taxa. A strong relationship was recovered between humerus and hindlimb allometric scaling and phylogeny. Our results indicate that while some ecological classes of modern birds can be discriminated from each other, phylogenetic signature can overwhelm ecological signal in morphometric data, potentially limiting the inferences that can be made from ecomorphological studies. Furthermore, we found differential scaling of leg bones among Early Cretaceous enantiornithines and ornithuromorphs, a result hinting that habitat partitioning among different lineages could be a pervasive phenomenon in avian evolution.